Invasive aspergillosis caused by Aspergillus non-fumigatus after allogeneic hematopoietic stem cell transplantation - V. V. Markelov; Yu. A. Rogacheva; M. O. Popova; A. G. Volkova; I. Yu. Nikolaev; O. N. Pinegina; A. A. Spididonova; S. M. Ignatieva; T. S. Bogomolova; O. V. Goloshchapov; Yu. Yu. Vlasova; E. V. Morozova; et al. (Журнал инфектологии)
Objective. To study the features of invasive aspergillosis (IA) due to A. non-fumigatus versus A. fumigatus in adult (≥ 18 years) recipients of allogeneic hematopoietic stem cell transplantation (allo-HSCT) in 2016-2021.   Materials and methods. The study included 33 patients with IA caused by A. non-fumigatus (n = 20) and A. fumigatus (n = 13). A comparative analysis of cases of IA, the results of therapy and outcomes in patients after allo-HSCT in the RM Gorbacheva Research Institute was performed. Diagnostic criteria EORTC / MSGERC 2020 were used.   Results. Invasive aspergillosis caused by A. non-fumigatus made up the majority (60.6 %) of IA cases with an identified pathogen registered in patients after allo-HSCT in the period from 2016 to 2021. The main etiological agents in the A. non-fumigatus group were A. niger in 13 (65 %) patients, A. flavus – in 4 (20 %). The median day of diagnosis of A. non-fumigatus IAwas + 110 days (17–2093), for A. fumigatus it was + 46 days (2–866) (p = 0.171). Overall 12-week survival was 55 % and 59.2 % in the A. non-fumigatus and A. fumigatus groups, respectively (p = 0.617). The majority of patients in both the A. fumigatus (n = 10, 77 %) and A. non-fumigatus (n = 16, 80 %) groups received voriconazole as initial antifungal therapy. Second-linetherapy was required in 2 (10 %) patients with A. non-fumigatus IA: liposomal amphotericin B and echinocandins with or with-out posaconazole, and 2 (15 %) patients in the A. fumigatus group: liposomal amphotericin B and voriconazole in combination with echinocandins. A comparative analysis showed that in patients from the two groups, none of the assessed signs (gender, age, underlying disease, disease status at the time of transplantation, time from diagnosis to allo-HSCT, source of hematopoietic stem cells, conditioning regimen, donor type, antifungal prophylaxis, cytomegalovirus reactivation, severe acute and chronic graft-versus-host disease) did not differ significantly.   Conclusions. A. niger is the main causative agent of IA caused by A. non-fumigatus. Patients characteristics, their treatment and outcomes did not differ significantly between the A. non-fumigatus and A. fumigatus groups.